Seminal Fluid-Mediated Inflammation in Physiology and Pathology of the Female Reproductive Tract - Anthonio O. Adefuye; Henry A. Adeola; Kurt J. Sales; Arieh A. Katz (Journal of Immunology Research)
Inflammation is a multifaceted process involving a host of resident and recruited immune cells that eliminate the insult or injury and initiate tissue repair. In the female reproductive tract (FMRT), inflammation-mediated alterations in epithelial, vascular, and immune functions are important components of complex physiological processes and many local and systemic pathologies. It is well established that intracoital and postcoital function of seminal fluid (SF) goes beyond nutritive support for the spermatozoa cells. SF, in particular, the inflammatory bioactive lipids, and prostaglandins present in vast quantities in SF, have a role in localized immune modulation and regulation of pathways that can exacerbate inflammation in the FMRT. In sexually active women SF-mediated inflammation has been implicated in physiologic processes such as ovulation, implantation, and parturition while also enhancing tumorigenesis and susceptibility to infection. This review highlights the molecular mechanism by which SF regulates inflammatory pathways in the FMRT and how alterations in these pathways contribute to physiology and pathology of the female reproductive function. In addition, based on findings from TaqMan® 96-Well Plate Arrays, on neoplastic cervical cells treated with SF, we discuss new findings on the role of SF as a potent driver of inflammatory and tumorigenic pathways in the cervix.